Evaluation Of Rice Husk Powder As An Anticaking Agent In Coffee Powder - Tan, Wei Ting (Universiti Sains Malaysia, 2020)
Synthetic anticaking agents have been widely used to solve powder caking. However, the increasing concern of consumers leads to the rising demand on clean labels. Potential natural ingredients such as rice husk which has high water adsorbing ability are yet to be studied and developed as anticaking agents. This study aims to evaluate the effectiveness of rice husk powder as an anticaking agent in coffee powder, specifically by characterisation, optimisation and study of moisture sorption isotherm. In this study, rice husk was milled into different size classes of powder (<75 μm, 75–250 μm and 250–500 μm). Characterisation was conducted based on silica content, fibre content, particle size and distribution, and particle morphology. Five samples prepared were control sample and coffee powder containing different amount of rice husk powder (1.0%, 1.7% and 3.0%) and 1.7% silicon dioxide (commercial reference). Samples were equilibrated with different relative humidities (23%, 43% and 62%) to prepare moisture-equilibrated samples. Anticaking properties were evaluated based on colour, moisture sorption isotherm and flowability. Rice husk powder had relatively high silica content and fibre content, with mean experimental values of 16.96% and 41.83% respectively. Size class of <75 μm had the greatest anticaking ability due to its smallest particle size and widest distribution. Particle morphology showed extensive layers of fibre-silica matrix with interlayer spaces. Relative humidity and amount of rice husk powder had significant impact on colour of the samples. Flowability increased with increasing amount of rice husk powder but decreased with increasing relative humidity.